Ciência, cultura e arte no planetário da UFRGS 2021-2024 - Merib, Rafael; Brugnera, Henrique; Klein, Brenda; do Lago Assumpção Vieira, Cassiana; Castro Oliveira, Jennifer; Paiva Conceição, Luciana; Baptista, Vanise; Romero, Alejandra (Revista da Extensão, 2024)
Ciência, cultura e arte no planetário da UFRGS 2021-2024